2015
DOI: 10.1016/j.mito.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Diseases Part II: Mouse models of OXPHOS deficiencies caused by defects in regulatory factors and other components required for mitochondrial function

Abstract: Mitochondrial disorders are defined as defects that affect the oxidative phosphorylation system (OXPHOS). They are characterized by a heterogeneous array of clinical presentations due in part to a wide variety of factors required for proper function of the components of the OXPHOS system. There is no cure for these disorders owing our poor knowledge of the pathogenic mechanisms of disease. To understand the mechanisms of human disease numerous mouse models have been developed in recent years. Here we summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 254 publications
(357 reference statements)
0
10
0
Order By: Relevance
“…This is supported by our observation that the same proportion of digitonin released the F1 subcomplex in the KO animals, but not in the controls. The appearance of F1 subcomplex of ATP synthase is also a characteristic feature of mtDNA maintenance defects in patients (Carrozzo et al, 2006), and was reported in numerous mouse models with impaired mtDNA expression owing to mtDNA replication defects (Milenkovic et al, 2013), impaired mtDNA transcription (Metodiev et al, 2009;Mourier et al, 2014;Park et al, 2007) or impaired mitochondrial translation (Cámara et al, 2011;Dogan et al, 2014;Iommarini et al, 2015;Szczepanowska et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by our observation that the same proportion of digitonin released the F1 subcomplex in the KO animals, but not in the controls. The appearance of F1 subcomplex of ATP synthase is also a characteristic feature of mtDNA maintenance defects in patients (Carrozzo et al, 2006), and was reported in numerous mouse models with impaired mtDNA expression owing to mtDNA replication defects (Milenkovic et al, 2013), impaired mtDNA transcription (Metodiev et al, 2009;Mourier et al, 2014;Park et al, 2007) or impaired mitochondrial translation (Cámara et al, 2011;Dogan et al, 2014;Iommarini et al, 2015;Szczepanowska et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Many of the models generated to date have utilized Cre/Lox technology to selectively knockout (KO) nuclear genes involved in: (i) mtDNA maintenance, replication, transcription, translation (ii) expression and assembly of OXPHOS complexes and (iii) mitochondrial dynamics to evaluate the effect on specific populations of neurons. A comprehensive description of these models is beyond the scope of the current review and we refer readers to a three part review miniseries published last year which discusses each model in detail .…”
Section: Modelling the Neurology Of Mitochondrial Diseasementioning
confidence: 99%
“…As such, this universal energy currency is synthesized at a rate of approximately 30 mM/min, with the majority originating from oxidative phosphorylation (Schmid et al, 2008 ). Defective mitochondria and decreased ATP synthesis are the hallmarks of numerous pathological conditions (Iommarini et al, 2015 ; Peralta et al, 2015 ; Torraco et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%